2018
DOI: 10.3389/fpls.2018.00222
|View full text |Cite
|
Sign up to set email alerts
|

New Generation of Resistant Sugar Beet Varieties for Advanced Integrated Management of Cercospora Leaf Spot in Central Europe

Abstract: Cercospora leaf spot (CLS) epidemics in sugar beet have been increasing in recent years causing higher use of fungicides. Concomitantly, the availability of effective fungicides is at risk because of resistance development in the fungus, the lack of new active ingredients as well as restrictive approval practices. A key option for an integrated management of CLS is cultivation of resistant varieties. Because of the yield penalty in resistant varieties, acceptance in commercial practice so far has been low. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…In line with these results, multiple resistances to fungicides with different modes of actions were also reported in other parts of Europe (Trkulja et al, 2017). In addition to fungicide application, the growth of sugar beet varieties with reduced susceptibility to C. beticola can support disease control (Varrelmann & Märländer, 2017;Vogel et al, 2018).…”
Section: Introductionsupporting
confidence: 64%
“…In line with these results, multiple resistances to fungicides with different modes of actions were also reported in other parts of Europe (Trkulja et al, 2017). In addition to fungicide application, the growth of sugar beet varieties with reduced susceptibility to C. beticola can support disease control (Varrelmann & Märländer, 2017;Vogel et al, 2018).…”
Section: Introductionsupporting
confidence: 64%
“…Inheritance of CLS resistance in sugar beet lines after introgression from wild sea beet is complex and has low heritability (Smith and Ruppel, 1974), while at the same time incorporation into high-yielding commercial sugar beet hybrids remains a challenge (Smith and Campbell, 1996). Promisingly, recent field trials in Germany showed that several European sugar beet varieties with CLS resistance lacked a yield penalty in the absence of disease and had better economic performance than susceptible varieties (Vogel et al, 2018). CLS resistance is typically managed by at least four identifiable quantitative trait loci (QTLs) (Smith and Gaskill, 1970;Nilsson et al, 1999;Setiawan et al, 2000;Taguchi et al, 2011).…”
Section: Host Resistancementioning
confidence: 99%
“…; Wann et al, 2017); and disease severity in wheat (Iqbal et al, 2016;Saintenac et al, 2018), sugar beet (Beta vulgaris L.; Kakueinezhad et al, 2018;Vogel et al, 2018), common bean (Amaro et al, 2007), and coffee (Coffea arabica L.; Botelho et al, 2017). ; Wann et al, 2017); and disease severity in wheat (Iqbal et al, 2016;Saintenac et al, 2018), sugar beet (Beta vulgaris L.; Kakueinezhad et al, 2018;Vogel et al, 2018), common bean (Amaro et al, 2007), and coffee (Coffea arabica L.; Botelho et al, 2017).…”
Section: New Proposals To Estimate Unbiased Selection Gain and Coeffimentioning
confidence: 99%
“…L. ; Wann et al, 2017); and disease severity in wheat (Iqbal et al, 2016;Saintenac et al, 2018), sugar beet (Beta vulgaris L.; Kakueinezhad et al, 2018;Vogel et al, 2018), common bean (Amaro et al, 2007), and coffee (Coffea arabica L.; Botelho et al, 2017). Usually, these score scales are treated as interval scales.…”
mentioning
confidence: 99%